Does Type, Quantity, and Location of Habitat Matter for Fish Diversity in a Great Plains Riverscape?. Issue 10 (8th July 2021) - Hitchman, Sean M.; Mather, Martha E.; Smith, Joseph M.
Abstract : Fisheries professionals frequently measure habitat type and amount, but less often measure the importance of where those habitats are located and in what combinations. We address this challenge by testing whether the individual and combined type, quantity, and location of habitat affects fish diversity in the upper Neosho River basin, Kansas, as a different approach to measuring habitat heterogeneity. Habitat type mattered in that species richness increased in areas of higher riffle density. Furthermore, variation within habitat type also influenced fish diversity; specifically, slower, shallower riffles had more species of fish. The spatial arrangement (i.e., impact of neighbor habitats) influenced fish diversity patterns in that riffle–run and riffle–glide pairings altered riffle habitat characteristics. The study illustrates a useful approach by measuring the type, amount, and arrangement of habitats to assess fish populations and could be adapted to other stream ecosystems.